Food Addiction and Its Relationship to Weight- and Addiction-Related Psychological Parameters in Individuals With Overweight and Obesity - Pape, Magdalena; Herpertz, Stephan; Schroeder, Stefanie; Seiferth, Caroline; Färber, Tanja; Wolstein, Jörg; Steins-Loeber, Sabine (Frontiers in Psychology, 2021)
Background and Aims: It is assumed that a relevant subgroup of individuals experiences an addiction-like eating behaviour (Food Addiction), characterized by an impaired control over eating behaviour, emotional eating and food craving. Individuals experiencing Food Addiction partially share common symptomatology with Binge-Eating-Disorder and Bulimia Nervosa. The aim of this study was to investigate the prevalence of Food Addiction, general psychopathology, and associations with weight- and addiction-related constructs in individuals with overweight and obesity, who did not suffer from Binge-Eating-Disorder or Bulimia Nervosa. Methods: N=213 (67.1% female) (MBMI=33.35kg/m², SDBMI=3.79kg/m²) participants who were included in a weight loss program (I-GENDO project) reported BMI and completed questionnaires before the start of the treatment. Food Addiction severity, depressive symptoms, alcohol use disorder, internet use disorder, psychological distress, impulsivity personality trait, impulsive and emotional eating behaviour, food related inhibitory control, weight bias internalization and self-efficacy were assessed. Results: The prevalence of Food Addiction was 15% with higher, although not statistically significant, prevalence in female (18.2%) compared to male (8.6%) participants. Food Addiction was associated with higher BMI at baseline assessment, low self-esteem, impulsive and emotional eating behaviour, weight bias internalization, and deficits in food-related inhibitory control. In addition, correlations were found between Food Addiction and severity of depressive symptoms, internet use disorder, and psychological distress. Conclusion: A relevant subgroup of participants experiences Food Addiction even when controlling for Binge-Eating-Disorder and Bulimia Nervosa. Future studies are warranted that investigate whether Food Addiction affects treatment success.